2020
DOI: 10.5812/ircmj.99920
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Prepositioning of Relief Items for Natural Disasters: A Systematic Review

Abstract: Context: Humanitarian logistics aims to reduce the suffering of disaster victims by fulfilling their immediate needs. A key component of humanitarian logistics is the prepositioning of relief items (such as water and food) for effective emergency response. Objectives: This study aimed to explore factors affecting the prepositioning of relief items for natural disasters. Data Sources: This was a systematic review. Relevant articles were retrieved from Google Scholar, PubMed, Web of Science, and Scopus databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They presented an integrated facility location problem, an inventory problem, and a distribution problem in humanitarian relief logistics when considering the inherent uncertainty of the input parameters. Sharifi-Sedeh et al [31] showed that a wide range of personal, managerial, professional, structural, environmental, and sociopolitical factors can affect the pre-positioning of relief items. Uncertainties about disasters, shortages of human, financial, and structural resources, lack of interorganisational agreements and collaboration, lack of clear protocols and guidelines and, most importantly, lack of thorough risk assessment studies were among the main factors behind pre-positioning the relief items.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They presented an integrated facility location problem, an inventory problem, and a distribution problem in humanitarian relief logistics when considering the inherent uncertainty of the input parameters. Sharifi-Sedeh et al [31] showed that a wide range of personal, managerial, professional, structural, environmental, and sociopolitical factors can affect the pre-positioning of relief items. Uncertainties about disasters, shortages of human, financial, and structural resources, lack of interorganisational agreements and collaboration, lack of clear protocols and guidelines and, most importantly, lack of thorough risk assessment studies were among the main factors behind pre-positioning the relief items.…”
Section: Literature Reviewmentioning
confidence: 99%